The Rate of Convergence of a Certain Mixed Monotone Difference Equation - Kulenović, Mustafa R.S.; Nurkanović, Mehmed; Nurkanović, Zehra (Sarajevo Journal of Mathematics, 2024)
This paper investigates the rate of convergence of a certain mixed monotone rational second-order difference equation with quadratic terms. More precisely we give the precise rate of convergence for all attractors of the difference equation x_n+1=Ax_n^2+Ex_n-1 x_n^2+f, where all parameters are positive and initial conditions are non-negative. The mentioned methods are illustrated in several characteristic examples. 2020 Mathematics Subject Classification. 39A10, 39A20, 65L20.